Deisgn of Mobile Infant Incubator with Comforting Pillow - Janney.J, Bethanney; KrishnaKumar, S; Shree.P.B, Anu; V, Rayshma; Suresh, Sanjana (International Journal of Engineering and Technology, 2018)
A mobile infant incubator is a preterm infant care medical tool which provides warmth, humidity and oxygen all in a controlled state of affairs as required by the New born baby. This incubator offers a clean condition, which has natural air, perfect and clean encompassing conditions for the infants. The main aim of the paper is to design and develop an Arudino based temperature and humidity control in an incubator.In the course of their initial weeks of lives infants are subjected to pain and soreness, so to conquerÂ this major problem we have introduced a mechanism to traject maternal features to the infant. For this reasons the features are mimicked viva a pillow unit that has embedded with sensors and actuators. Our proposed system consists of sensors for monitoring critical parameters, Pillow unit for comforting the infants, GSM for transferring information to doctors and parents and Labview for output evaluation and all together controlled by Arudino microcontroller. Advances in electronic procedures combined with sparing costs influence humidity and temperature toÂ govern realistic with fantastically precise and solid performance.Â Â